DYNAMICAL SIMULATION OF A VALVETRAIN MECHANISM: AN ENGINEERING EDUCATION APPROACH - Nunes, M. A. A.; Silva, R. C.; Oliveira, A. B. S.; Peron, G. C. (Revista de Engenharia Térmica, 2013)
The present work aims to present a valvetrain model considering the dynamics functioning aspects of an Otto’s engine. The model will be constructed using Adams/View® software, which is a powerful modeling and simulating environment of dynamic systems. It allows building, simulating, refining and optimizing any mechanical system. In fact, the model will help engineering students to understand how the mechanism works, in terms of displacement, velocity and acceleration of the valve as a function of the time. It is also possible to know the behavior of the force in the spring as a function of the time and, finally, the torque applied in the cam due to a angular velocity input. Relative to spring force, during the Otto engine cycle, the cam lobe must be able to open and close the valve as fast and as smoothly as possible. The force responsible to close the valve is applied by the valve spring, which is also responsible for keeping contact between the cam lobe and the valve. Dynamic forces impose limits on cam and valve lift. Thus, the simulation model allows determining these forces and displacements through the cam rotation. As main objectives the authors wish to make available a model which is capable to show in 3D the animation of a valvetrain mechanism of an Otto engine, obtaining the main curves for analysis and evaluation of this mechanism performance.